ESG Reporting as Tool to Improve Access to Finance in South Asian Businesses: A Critical Review - D.P.M.S.M. Peiris; H.D.I. Silva (Canadian Journal of Business, Economics and Health Management, 2026)
ESG reporting is increasingly recognized as a tool for corporate transparency and financial legitimacy, yet its role in facilitating access to finance in South Asia remains underexplored. This paper examines how ESG reporting is conceptualized, synthesizes evidence on its impact on finance, identifies contextual factors shaping this relationship, and proposes a conceptual model for South Asian firms. A structured critical literature review was conducted, analyzing peer-reviewed articles, policy reports, and empirical studies on ESG reporting and access to finance in South Asia. Conceptual, empirical, and institutional insights were synthesized to develop a region-specific framework. ESG reporting generally improves access to finance, lowering capital costs, enhancing credit terms, and boosting investor confidence. In South Asia, however, these benefits depend on regulatory enforcement, institutional quality, assurance mechanisms, and market maturity. Weak governance and greenwashing limit ESG’s financial impact. Policymakers and financial institutions should strengthen disclosure standards, promote independent assurance, and improve enforcement. Firms can use high-quality ESG reporting to signal lower risk and attract better financing conditions. Enhanced ESG reporting can foster sustainable financial systems, promoting environmental protection, social inclusion, and long-term economic resilience in South Asia. This study offers one of the first South Asia–specific syntheses of ESG reporting and finance, integrating institutional, economic, and socio-cultural factors into a multi-level conceptual model for emerging markets.